RESISTENSI DALAM NOVEL STUDENT HIDJO KARYA MAS MARCO KARTODIKROMO: KAJIAN POSKOLONIAL - Nando Zikir Mahattir; Novi Anoegrajekti; Abu Bakar Ramadhan Muhamad (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2021)
This research use Mas Marco's novel Student Hidjo as material object. The Postcolonial theory will be used to analys Student Hidjo novel’s by Mas Marco. Postcolonial is a set of theories to explore the effects of colonialism in various documents and behaviors, including literature. This study uses qualitative methods to obtain the necessary data from the novel. This type of analysis uses descriptive analysis. The analysis will use deconstruction method. This is in accordance with postcolonialism which is a reversal of the colonial discourse. Such a method is useful for reversing the colonial discourse which presents the relationship between colonizers >< colonized in the novel.. The relationship that seemed stable was undermined by the subjectivity of the colonized through their resistance. The various resistances presented by the colonized were understood by the postcolonialists as a form of an ambivalent legacy of colonialism. The ambivalent side occurs because the resulting resistance strikes both sides. On the one side attacking the invaders, but on the other side attacking resisting subject. Keywords: postcolonial, deconstruction, colonizers, colonized, ambivalent